The Trinity of Christianity in the Context of Religious Dialogue - ZHENG, Nada (Journal of Research for Christianity in China (JRCC), 2025)
The attribute of more in one of Trinity breaks through the natural exclusiveness of absolute monotheism, and the roles and functions of different persons give the support of dogmatic theory for the possibility of the dialogue between Christianity and the other religions. Although the Trinity has been accepted by Christianity as the basic doctrine, the situations and ideas of different eras always made debates for the Trinity, in order that the theory of the Trinity has often been understood and interpreted in different views. And then, the Trinity has the potential of being meaningfully expressed in the context of the pluralistic dialogues during religions. Therefore, the doctrine of the Trinity has become the resource of theory for the Christianity who wants to stand firmly in different forms of dialogues of religions while the Christianity is meeting, communicating and talking with other religions.